Screening and Identification of Lactic Acid Bacteria from Livestock Rumen as Probiotic Candidates - Widianingrum, Desy Cahya; Tanzil, Ahmad Ilham; Masnilah, Rachmi; Nurcahyanti3, Suhartiningsih Dwi; Fitriani, Vivi; Khasanah, Himmatul (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Population of lactic acid bacteria (LAB) in the rumen of fattening livestock is relatively high and has the potential to be utilized. This study aimed to screen and identify LAB from the rumen as probiotic candidates. The research used rumen liquid from cattle, goats, and sheep collected from slaughterhouses in Bondowoso. The screening and identification processes were conducted at the Livestock Agroindustry Laboratory, Faculty of Agriculture, University of Jember. The screening included colony morphology, Gram staining, cell shape, catalase test, and Carbon dioxide (CO2) gas production ability. The final identification of potential probiotic bacterial candidates was based on their bile salt tolerance. The results showed that there were LAB candidates with 22 isolates (from sheep/OS), 19 isolates (from cattle/OC), and 18 isolates (from goats/OG). The bacterial colony shape included oval (2OS, 1OC), circular (11OS, 18OC, 12OG), irregular (7OS, 6OG), and spindle (2OS). Colony sizes ranged from small (0.5–1.2 mm: 7 OS, 9OC, 4OG), medium (1.2–3.0 mm: 7OS, 7OC, 7OG), to large (3.0–5.0 mm: 8OS, 3OC, 7OG), with the majority of colonies being white and cream-colored, and a minority being yellow. All bacteria were Gram-positive, with coccus (19OS, 14OC, 2OG) and bacillus (3OS, 5OC, 16OG) shaped cells. All samples were capable of producing CO2 gas, and 50% of the isolates possessed catalase enzymes. Based on bile salt tolerance tests, 15% of the isolates had a survival rate of over 50%. In conclusion, LAB from the rumen, particularly goats, were identified as potential probiotic candidates for further development.